1991
DOI: 10.1002/ptr.2650050603
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pollen extracts on prolonged poisoning of rats with organic solvents

Abstract: Male Wistar rats were divided into four equal groups: (i) controls, (ii) animals exposed to organic solvents, (iii) animals exposed to organic solvents and receiving pollen extracts, (iv) rats given pollen extracts. The experiment lasted 3 months. The protective effect of pollen extracts against changes evoked by organic solvents was demonstrated. Pollen extracts inhibited or counteracted the elevation of aminotransferases and alkaline phosphatase activity and lipid and carbohydrate metabolism disturbances in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
(9 reference statements)
3
2
0
Order By: Relevance
“…In accordance with our results, Attia et al (2011a; and Ceglecka (1991) found that rats supplemented with 60 mg of pollen extracts per kg BW significantly decreased liver-enzyme levels compared to control. The cytotoxic effect as indicated by liver damage in the control rats increased their plasma cholesterol by 104% and triglycerides by 37%, whereas these increases were all but prevented in rats given pollen extract.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with our results, Attia et al (2011a; and Ceglecka (1991) found that rats supplemented with 60 mg of pollen extracts per kg BW significantly decreased liver-enzyme levels compared to control. The cytotoxic effect as indicated by liver damage in the control rats increased their plasma cholesterol by 104% and triglycerides by 37%, whereas these increases were all but prevented in rats given pollen extract.…”
Section: Discussionsupporting
confidence: 92%
“…The present results are in line with those reported by Attia et al (2010) and Ceglecka et al (1991) who found that treatment of rats with 60 mg pollen extracts/kg BW significantly decreased liver-enzyme levels than the control group. The cytotoxic effect as indicated by liver damage in the control rats increased their serum cholesterol by 104% and triglycerides by 37%, such increases were nearly prevented in rats given pollen.…”
Section: Bee Pollen Effectssupporting
confidence: 96%
“…Attia et al () reported that supplementation of BP (200 mg/kg BW) or/and Propils (200 mg/kg BW) to rabbit diets significantly ( p < 0.01) decreased the serum values of liver enzymes (ALT, AST and AST/ALT). Similar results were obtained by Ceglecka et al () who stated that rats supplemented with pollen extracts (60 mg/kg BW) showed significantly reduced levels of liver enzymes compared to the control. From the above, it is clear that BP declined liver damage and enhanced liver function.…”
Section: Beneficial Effects Of Bpsupporting
confidence: 89%